The Influence of Promotion and Product Quality on Competitive Advantage: Study on CV. Putri Bungsu - Siti Nabila Rasida; Anisah, Hastin Umi (HM Publisher, 2024)
Promotion indeed acts as a medium to convey information to the public regarding the benefits in the form of added value derived from the quality of the company's products. This helps the company's competitive advantage. Competition between distributors of various cement brands is only more dominant in marketing strategy and product quality. Therefore, the researcher took two points from the marketing mix, namely promotion and product quality, as variables that influence competitive advantage. This emphasizes that companies with marketing mix strategies in conveying information to the public through promotions have adequate product quality in the context of competitive advantage. This research aims to analyze the influence of promotion and product quality on competitive advantage. This research was conducted on a CV. Putri Bungsu, which is the official distributor company of PT. Conch South Kalimantan Cement. This type of research is quantitative research, with the sampling method used in this research being purposive sampling carried out on CV. Putri Bungsu customers. This research derived two hypotheses, which were tested using SPSS. The research results show that Promotion has a significant positive effect on competitive advantage and product quality has a significant positive effect on competitive advantage.